Analisis Preferensi Pengguna dari Kesan Visual Desain Interior Kompartemen Kereta Api New Generation dengan Metode Kansei Engineering (Politeknik Perkeretaapian Indonesia Madiun, 2022)
This study discusses the visual impression of the interior design of the new generation train compartment based on user preferences by using the Kansei engineering method as a form of innovation that is continuously being pursued by PT. INKA (Persero) to accommodate the high public interest in rail transportation. The purpose of this study is to determine the items and categories of interior design compartments based on user preferences. Data were collected through observation, interviews, and questionnaires and then analyzed using validity and reliability tests, as well as multiple linear regression tests. The results obtained are 6 kansei words, namely comfortable, luxurious, pleasant, unique, simple, and modern. While the results of the regression test indicate the influence of the independent variable simultaneously on the dependent variable. The most popular design is the D03 design which has the visual impression of a minimalist theme, a green color palette, painting decorations, glossy, and HPL wood motif dominant finishing.